2010
DOI: 10.1145/1721933.1721951
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of distributed pair programming for an online informatics curriculum

Abstract: Studies have shown that distributed pair programming improves student performance and retention in online computer science (CS) courses. However, as online CS courses become more commonly offered in computer science and Informatics departments around the country, it is imperative that distributed pair programming becomes as effective as when performed in co-located spaces such as computer labs. The present study identifies a disparity in student attitudes towards pair programming in co-located versus online en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…This distinction is important, since colocation enables students to establish a connection in a face-to-face context and then use online tools to do DPP. This gap in the research has also been noted by Edwards et al (2010), who called for more comprehensive and intensive investigation into the power of pair programming when used within purely online courses.…”
Section: Distributed Pair Programmingmentioning
confidence: 99%
“…This distinction is important, since colocation enables students to establish a connection in a face-to-face context and then use online tools to do DPP. This gap in the research has also been noted by Edwards et al (2010), who called for more comprehensive and intensive investigation into the power of pair programming when used within purely online courses.…”
Section: Distributed Pair Programmingmentioning
confidence: 99%
“…Assessing methods used in programming education is scoring student source codes and give students feedbacks of the wrong points in the source codes [1][2][3][4]. By these methods, a student may not be able to correct her wrong points since the errors may come from her understanding gaps.…”
Section: Failure Of Present Assessing Methodsmentioning
confidence: 99%
“…Students also indicated that it would be more interesting to use DPP synchronously through specific tools that facilitate the communication between the pairs. The study conducted by Edwards et al [EDW10] aimed to evaluate DPP effectiveness in the curriculum of a Computer Science course. At the end of the course, students answered a survey about their performance.…”
Section: Teachingmentioning
confidence: 99%
“…As DPP is a derived from PP, most of the studies aimed to compare the efficiency between both practices such as observed in [BAH02], [CAN03], [CAN06] and [EDW10]. Some of the studies have a focus in comparing DPP with solo (individual) programming, as identified in [ZAC11] and [DUQ08].…”
Section: Dpp and Other Types Of Programmingmentioning
confidence: 99%
See 1 more Smart Citation